Face Perception Predicts Affective Theory of Mind in Autism Spectrum Disorder but not Schizophrenia or Typical Development - Altschuler, Melody R. (J Abnorm Psychol, 2021)
Autism spectrum disorder (ASD) and schizophrenia spectrum disorder (SCZ) have overlapping symptomatology related to difficulties in social cognition. Yet, few studies have directly compared social cognition in ASD, SCZ, and typical development (TD). The current study examined individual differences in face recognition and its relation to affective Theory of Mind (ToM) in each diagnostic group. Adults with ASD (n = 31), SCZ (n = 43), and TD (n = 47) between the ages of 18 and 48 with full scale IQ above 80 participated in this study. The Reading the Mind in the Eyes Task (RMET) measured affective ToM, and the Benton Facial Recognition Test (BFRT) measured face perception. Adults with ASD and SCZ did not differ in their affective ToM abilities, and both groups showed affective ToM difficulties compared to TD. However, better face recognition ability uniquely predicted better affective ToM ability in ASD. Results suggest that affective ToM difficulties may relate to face processing in ASD but not SCZ. By clarifying the complex nature of individual differences in affective ToM and face recognition difficulties in these disorders, the present study suggests there may be divergent mechanisms underlying pathways to social dysfunction in ASD compared to SCZ.